The impacts of violence among women in intimate relationships: an integrative literature review - Mota, Fabiana Lobo [UNESP]; de Almeida, Margareth Aparecida Santini [UNESP]; Machado, Dinair Ferreira [UNESP] (FapUNIFESP (SciELO), 2024)
The aim is to identify cultural, social and health impacts caused by intimate partner violence (IPV) in homoaffective (MOH) and bia-ffective (MOB) women. This is an integrative literature review that sought and analyzed studies indexed in the PubMed and Lilacs databases, considering the following languages. The study sought to answer the following research question: “What impacts does IPV bring to MOB and MOH?”. Forty two studies were found and after applying the exclusion criteria, 19 went into the fi-nal sample. Data were analyzed using the content analysis methodology, Bardin’s thematic analysis modality (2009). The full analysis of the articles revealed two categories: 1) Intimate partner violence and sociocultural impacts; and 2) Intimate partner violence and health impacts. The experience of situations of violence in intimate partnerships between homo and/or biaffective women affect their sociocultural and health dimensions, since they are under the bias of double vulnera-bility: women in homo/biaffective relationships. There is also an invisibility of the phenomenon in health services, since professionals are not trai-ned to address the different sexual orientations among women and even less the situations of violence resulting from these relationships.
Os impactos da violência entre mulheres em relação íntima: uma revisão integrativa da literatura
Keywords: Female homosexuals; IPV; Sexual and gender minorities; Violence against women